Hubungan Pemanfaatan Fasilitas Belajar Di Rumah Dengan Hasil Belajar Matematika Kelas IV Madrasah Iibtidaiyah Baeturridlwan - Safiatuddin, Nasa Benaisa; Nasihudin, Nasihudin; Rahman, Alvin Yanuar (Universitas Negeri Surabaya, 2024)
The utilization of learning facilities at home is something that is related to student learning outcomes. One of the learning outcomes is math. Class IV MI Baeturridlwan in learning mathematics when learning there are students who are enthusiastic and some are not. Then there are students who do not have complete stationery. Then there are still students who do not have exercise books in their homes. Therefore, researchers are interested in conducting research related to the relationship between the utilization of learning facilities at home and the mathematics learning outcomes of grade IV students of MI Baeturridlwan. The purpose of this study was to analyze the relationship between the utilization of learning facilities with children's learning outcomes in mathematics. The research method used in this research is descriptive method with quantitative approach. The data collection techniques are questionnaires and documentation. The data analysis technique in this study consists of associative statistics with the correlation coefficient test. The hypothesis in this study is Ho: There is no relationship between the utilization of learning facilities at home and children's learning outcomes in mathematics lessons at Baeturridlwan Madrasah Ibtidaiyah. Ha: There is a relationship between the utilization of learning facilities at home with children's learning outcomes in mathematics at Baeturridlwan Madrasah Ibtidaiyah. The results of this study indicate that there is no relationship between the utilization of learning facilities at students' homes and students' mathematics learning outcomes. Proven by the results of the correlation test analysis, it is known that rcount is -0.363 and rtable is 0.388 or -0.388. Then Ho is accepted with the test criteria -0.388 ? -0.363 ? 0.388. The absence of this relationship can be caused by the mathematics learning outcomes of MI Baeturridlwan students still vary and the majority of the score range is low. Keywords: Learning Facilities, Madrasah Ibtidaiyah, dan Mathematics